Etiologije črnih koz in vakcinacija - Krivec, Jaroš (Filozofski vestnik, 2025)
The study focuses on one of the main reasons for the rejection of early vaccination, which is in fact linked to the understanding of smallpox disease itself. Because of its course, speed of spread and mortality rate, this infectious disease has been considered one of the worst scourges of mankind, but it is also the only human infectious disease to have been eradicated, with prophylactic vaccination playing a key role. This study will explore the understanding of variola in an era not yet based on knowledge of pathogenic microbes as disease-causing agents. The paper will show that ordinary people and physicians expressed plural perceptions of variola, which could be changing, mutually exclusive but also mixed. The main conclusion of the paper is that the perception of variola as an innate necessity that purifies the body has acted as one of the main reasons for the rejection of vaccination.
Keywords: anti-vaccination; cepljenje; črne koze; Habsburg monarchy; Habsburška monarhija; history of science; proticepilstvo; smallpox; social history of medicine; socialna zgodovina medicine; vaccination; zgodovina znanosti